DARI NALAR FIKIH MENUJU NALAR UNDANG-UNDANG (TRANSFORMASI HUKUM ISLAM KE DALAM LEGISLASI NASIONAL) - Marzuki Marzuki (Hunafa: Jurnal Studia Islamika, 2006)
It is not easy to make a definition of “law” since Islamic syari’ah, Islamic law and fiqh are  law in nature. Basically, in a society, law aims at serving and protecting society. It is a system of implementation to protect both individual rights and societal rights. Besides, it possesses nature and scope of its own. Law is constant. It is not influenced by room and time. It is only Muslim’s interpretation to the law that always changes in accordance with socio-historical and cultural spheres. Islamic syari’ah, Islam law and fiqh, lie on the argument used. Islamic syari’ah is based on the Qur’an and the Sunnah without any legal reasoning, but constantly relies on the spirit of the two Islamic sources. So, Islamic syari’ah is constant while Islamic law is temporal. In the context of positive law, Islamic law has good prospect as long as law practitioners are capable of optimizing the strength and opportunity possessed by Islamic law.    Kata Kunci:  Undang-undang, syari’ah, hukum Islam